TECHNOLOGY OF IDENTIFYING EDUCATIONAL LEVELS ACCORDANCE AS INNOVATIVE APPROACH IN EDUCATIONAL SYSTEM - Filatova, Т.В. (Journal of Information Technologies in Education (ITE), 2015)
The problem of raising the quality level of education determines the achieving new qualification levels of applicant for education. Universities, colleges, schools are interested in improving transition between qualification levels. The desire to improve the education system, the innovative use of advanced models and information technology leads to the improvement of the educational system as in Ukraine so in the other countries. It is desirable for solving this problem to do the curriculum in a single universal kind. The first, it's necessary to do inside one Higher School (HS) and after inside the city, the country and at the international level. Therefore, the situation presented in the educational process requires optimization. For this we have to formulate and automate the transition within borders of given problem. Bringing this to universal kind will help to solve a number of problems during the transition even at the international level. This can be achieved by grouping the educational programs into an ordered series of categories. The compliance curriculum of different specialties will highlight exactly the group in which it is possible to continue further education. This technology will allow the bachelors to elect another specialty of the HS and applied if appropriate discipline of vocational education is not sufficient for admission to desired specialty.